Comparing the Gettering Effect of Heavily Doped Polysilicon Films and Its Implications for Tunnel Oxide‐Passivated Contact Solar Cells. Issue 8 (28th April 2023) - Yang, Zhongshu; Krügener, Jan; Feldmann, Frank; Polzin, Jana-Isabelle; Steinhauser, Bernd; Aleshin, Matvei; Le, Tien T.; Macdonald, Daniel; Liu, AnYao
Abstract : Tunnel Oxide‐Passivated Contact Solar Cells In article number 2200578, Zhongshu Yang, AnYao Liu and co‐workers investigated and compared the gettering effects and mechanisms of a range of P‐ or B‐doped poly‐Si/SiOx passivating contacts and assessed the impact of gettering during the poly‐Si/SiOx fabrication process on tunnel oxide‐passivated contact solar cell performance.